A detailed review on the performance of photovoltaic/thermal system using various cooling methods. (June 2022) - Pathak, Sudhir Kumar; Sharma, Pravin Omprakash; Goel, Varun; Bhattacharyya, Suvanjan; Aybar, Hikmet Ş.; Meyer, Josua P.
Abstract: As an emerging technology, photovoltaic (PV) panels have made a vital energy source to meet increased energy consumption demand and to replace the associated scarcity of traditional energy resources. PV modules have electrical efficiency from 4 to 26%, depending on their materials. The PV panel transforms about 50–60% of total solar radiation into heat, leading to high temperatures during the operation of the PV panel. Due to high temperature, there is a decrease in electrical conversion efficiency and thermal stress in PV panels continue for a more extended period. In this context, a photovoltaic/thermal (PV/T) system is suggested to decrease the thermal stress of the PV panel by removal of heat and make it useful at high PV module temperature. This comprehensive literature review reports PV cooling techniques, research gaps and difficulties encountered by various researchers in this technology. To counter this drawback, active and passive methods of cooling have been studied, including jet impingement, airflow cooling, immersion cooling using liquids, thermoelectric based cooling, microchannel cooling, phase change materials (PCM) based cooling, water/liquid cooling and heat pipe cooling. This research study intends to present a modern, systematic review of PV/T cooling techniques and challenges associated with these methods. Furthermore, techno-economic analysis and the role of artificial intelligence in PV/T systems are also summarized.